2022
DOI: 10.3399/bjgpo.2022.0100
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of prior spontaneous miscarriage on stress among pregnant women during the first trimester: an observational study

Abstract: BackgroundSpontaneous miscarriage is the most common complication of pregnancy. Its psychological repercussions are widely documented but few studies have investigated its effect on the woman’s experience of a subsequent pregnancy.AimTo evaluate the impact of prior spontaneous miscarriage on the level of stress experienced by pregnant women during the first trimester of pregnancy.Design and settingCross-sectional, observational study between June and October 2021 in France.MethodA self-report questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…Fertl et al reported that women who had a history of spontaneous pregnancy loss had higher levels of anxiety during the first trimester of subsequent pregnancy, compared to women with no history of miscarriage [21]. In a French study by Barbe et al, it was found that during the first trimester of pregnancy, women with a history of spontaneous miscarriage had higher stress levels relating to the medical and obstetric risks or fetal health, than women with no history of miscarriage [22]. Similarly, Haghparast et al showed that pregnant women who had a history of spontaneous abortion during the previous year had higher scores on anxiety and depression scales (amongst others) compared to pregnant women without a history of spontaneous abortion [23].…”
Section: Introductionmentioning
confidence: 99%
“…Fertl et al reported that women who had a history of spontaneous pregnancy loss had higher levels of anxiety during the first trimester of subsequent pregnancy, compared to women with no history of miscarriage [21]. In a French study by Barbe et al, it was found that during the first trimester of pregnancy, women with a history of spontaneous miscarriage had higher stress levels relating to the medical and obstetric risks or fetal health, than women with no history of miscarriage [22]. Similarly, Haghparast et al showed that pregnant women who had a history of spontaneous abortion during the previous year had higher scores on anxiety and depression scales (amongst others) compared to pregnant women without a history of spontaneous abortion [23].…”
Section: Introductionmentioning
confidence: 99%